Urotensin receptor acts as a novel target for ameliorating fasting-induced skeletal muscle atrophy. (November 2022) - Yin, Lin; Li, Na; Jia, Weihua; Wang, Nuoqi; Liang, Meidai; Shang, Jiamin; Qiang, Guifen; Du, Guanhua; Yang, Xiuying
Abstract: Urotensin receptor (UT) is a G-protein-coupled receptor, whose endogenous ligand is urotensin-II (U-II). Skeletal muscle mass is regulated by various conditions, such as nutritional status, exercise, and diseases. Previous studies have pointed out that the urotensinergic system is involved in skeletal muscle metabolism and function, but its mechanism remains unclear, especially given the lack of research on the effect and mechanism of fasting. In this study, UT receptor knockout mice were generated to evaluate whether UT has effects on fasting induced skeletal muscle atrophy. Furthermore, the UT antagonist palosuran (3, 10, 30 mg/kg) was intraperitoneally administered daily for 5 days to clarify the therapeutic effect of UT antagonism. Our results found the mice that fasted for 48 h exhibited skeletal muscle atrophy, accompanied by enhanced U-II levels in both skeletal muscles and blood. UT receptor knockout effectively prevented fasting-induced skeletal muscle atrophy. The UT antagonist ameliorated fasting-induced muscle atrophy in mice as determined by increased muscle strengths, weights, and muscle fiber areas (including fast, slow, and mixed types). In addition, the UT antagonist reduced skeletal muscle atrophic markers, including F-box only protein 32 (FBXO32) and tripartite motif containing 63 (TRIM63). Moreover, the UT antagonist was also observed to enhance PI3K/AKT/mTOR while inhibiting autophagy signaling. In summary, our study provides the first evidence that UT antagonism may represent a novel therapeutic approach for the treatment of fasting-induced skeletal muscle atrophy. Graphical Abstract: ga1